Running crabs, walking crinoids, grazing gastropods: behavioral diversity and evolutionary implications in the Cabeço da Ladeira lagerstätte (Middle Jurassic, Portugal) - Carvalho, Carlos Neto de (2016)
Ichnology is a powerful tool for understanding the evolutionary paths of animal clades, through the paleobiology of behavior preserved in Lagerstätten such as the Cabeço da Ladeira (Portugal) site. Here, the peritidal carbonates of the Chão das Pias Formation (Middle Jurassic, upper Bajocian) record the development of microbial mats in a tidal flat. Episodically, the flat was expanded during periods of equinoctial spring tides that may have been responsible for the in situ killing of several members of echinoderm clades, and the fine preservation of their endoskeleton, in addition to the behavior of an arthropod-dominated endo- and epifauna. Mat-preserved shallow tiers with a moderate ichnodiversity attributed to the Cruziana ichnofacies include trackways of crabs (Laterigradus lusitanica igen. nov., isp. nov.) and shrimps ( Diplopodichnus isp.); trails of fishes (?Undichna), gastropods (Archaeonassa fossulata), isocrinid crinoids (Krinodromos bentou igen. nov., isp. nov.) and insects (Haplotichnus indianensis); and burrows of shrimps or lobsters (Thalassinoides suevicus) and other arthropods (Asterosoma ludwigae, Gyrochorte comosa), or polychaetes (Rhizocorallium commune ). This is implied already above (igen. nov., etc.) and seems not needed. The crab trackways and gastropod bulldozing trails, extending up to 12.3 m, are among the longest invertebrate cursorial traces ever found in the fossil record. The mortichnial crawling trail of a crinoid is the first evidence of locomotion for this group in the fossil record, and a rare unambiguous example of this ethology. Extensive continuous trackways attributed to amphibious crabs record, with great detail, typical gaits of underwater punting and walking sideways on dry land. The earliest evidences of sidewalking behavior may also be evidence for the development of the crab form during their rise in the Jurassic.